Acceptance level towards block buster deals product by Telekom Malaysia / Leorna Joanne L.N Tinun - L.N Tinun, Leorna Joanne (2011)
The issue of this study is to identify the acceptance level towards Block Buster Deals product by Telekom Malaysia Berhad. Nowadays, Telekom Malaysia has to compete with other telecommunication services provider in the market such as Celcom, Digi and Maxis. In order to compete with the other competitor, Telekom Malaysia come out with one package that known as Block Buster Deals that have own advantage or specialty with the package that can attract customer to purchase the services. In this study, been conduct to fulfill the customer perception towards the Telekom Malaysia package and the acceptance of consumer on the product itself. Consumer perception on the product beside the other telecommunication services provider in the market whereby consumer more prefer Telekom Malaysia product beside other in the market. On the study, researcher find the population based on public and also the Telekom Malaysia customer that use the personal Homeline and Streamyx at home that drop by at the TM Point. Researcher find out that, most of the consumer still using a Telekom Malaysia product until now. Besides that, consumers aware of the Block Buster Deals Package had been introducing in the market. Apart of the study, researcher found that the independent variable of the acceptance of consumer on a product are product, performance and price of the product or services itself.